Formation of 3-deoxyglucosone in the malting process. (30th August 2019) - Nobis, Arndt; Röhrig, Anne; Hellwig, Michael; Henle, Thomas; Becker, Thomas; Gastl, Martina
Highlights: 3-Deoxyglucosone is formed over the kilning process. Technologically malting conditions have influence on the final 3-deoxyglucosone amount in malt. High levels of malt modification and final kilning temperature increase the final 3-deoxyglucosone amount in malt. A kilning model proved formation of 3-deoxyglucosone formation from glucose under malting model conditions. 3-Deoxyglucosone is already formed in comparable high contents to mash, wort and beer. Abstract: 3-Deoxyglucosone (3-DG) is a metabolite from sugar degradation obtained by the Maillard reaction. It is an important precursor compound in Strecker reactionism that directly leads to known beer aging indicators and can influence the final sensory beer quality. However, the conditions of 3-DG formation in the malting process have not yet been described. To investigate the reaction pathways of 3-DG formation, we varied the composition of reactants (sugars, amino acids) by using different malting modification levels (germination time 5–7 d; steeping degree 42–45%; germination temperature 12–14 °C); final kilning temperature (60 °C to 100 °C). After its derivatization with ortho-phenylenediamine, we analyzed 3-DG with HPLC-UV. 3-DG concentration was between 5 and 120 µmol/100 g dry weight. The formation of 3-DG increased for high malt modification levels and high final kilning temperature. The abundant formation of 3-DG in the malting process is already comparable to the occurred brewing process concentration.